2019
DOI: 10.1080/20018525.2019.1702618
|View full text |Cite
|
Sign up to set email alerts
|

Forced Vital Capacity (FVC) decline, mortality and healthcare resource utilization in idiopathic pulmonary fibrosis

Abstract: Aim of the study: Potential care implications of antifibrotic reimbursement restrictions were studied by forced vital capacity (FVC) decline, mortality and specialty care related healthcare resource utilization in patients with idiopathic pulmonary fibrosis (IPF). Material and methods: IPF patients were identified from the electronic medical records of the Hospital District of Southwest Finland between 2005 and 2017. Text-mining was used for patient identification to exclude other interstitial lung diseases (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Our joint model approach using data from the SENSCIS® trial showed that a decline in FVC% predicted corresponded to a statistically significant increase in the risk of all-cause and SSc-related hospitalisation or death during the treatment period. This is a new finding in SSc and is consistent with data in IPF [ 28 ]; it is also clinically important since hospitalisation rate is one of the most important outcomes for patients. We also observed a statistically significant treatment effect of nintedanib on FVC decline, mirroring the results from the SENSCIS® trial in which nintedanib reduced the rate of FVC decline compared with placebo [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our joint model approach using data from the SENSCIS® trial showed that a decline in FVC% predicted corresponded to a statistically significant increase in the risk of all-cause and SSc-related hospitalisation or death during the treatment period. This is a new finding in SSc and is consistent with data in IPF [ 28 ]; it is also clinically important since hospitalisation rate is one of the most important outcomes for patients. We also observed a statistically significant treatment effect of nintedanib on FVC decline, mirroring the results from the SENSCIS® trial in which nintedanib reduced the rate of FVC decline compared with placebo [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our joint model approach using data from the SENSCIS® trial showed that a decline in FVC% predicted corresponded to a statistically signi cant increase in the risk of all-cause and SSc-related hospitalisation or death during the treatment period. This is a new nding in SSc and is consistent with data in IPF [30]; it is also clinically important since hospitalisation rate is one of the most important outcomes for patients. We also observed a statistically signi cant treatment effect of nintedanib on FVC decline, mirroring the results from the SENSCIS® trial in which nintedanib reduced the rate of FVC decline compared with placebo [20].…”
Section: Discussionsupporting
confidence: 85%
“…Some patients develop the scarring slowly and bear with the disease for several years, whereas others deteriorate more quickly, leading to death [ 3 ]. When scarring occurs, the patient finds it difficult to breathe normally, which eventually leads to shortness of breath even when the person is not performing any strenuous exercise [ 4 ]. Patients with this disease display fibrotic sections, honeycombing, and wide-ranging patchy ground-glass areas with or without consolidations, depicting the presence of pleural fluid within the CT scans [ 5 ].…”
Section: Introductionmentioning
confidence: 99%